2003
DOI: 10.1046/j.1365-2435.2003.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Foraging effort in relation to the constraints of reproduction in free‐ranging albatrosses

Abstract: Summary1. Theoretical models predict that animals will vary their effort to maximize different currencies such as time and energy when the constraints of reproduction change during breeding, but this has been poorly studied in free-ranging animals. 2. Foraging effort (energy per unit time) was examined by comparing mass changes, foraging costs and activity-specific behaviours of Wandering Albatrosses ( Diomedea exulans Linnaeus) during the incubation and chick-brooding stages. In 1998, 38 albatrosses (20 durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
111
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 43 publications
2
111
2
Order By: Relevance
“…Surprisingly, we did not find differences in dive frequency between incubation and late chick-rearing, even though several studies suggested an increase of parents foraging effort during chick-rearing (Shaffer et al 2003;Navarro et al 2007). Nevertheless, these studies considered chick-rearing as a single phase covering possible differences in birds' foraging activity over it.…”
Section: Effect Of Phase and Trip Type On Foraging Effortcontrasting
confidence: 79%
See 2 more Smart Citations
“…Surprisingly, we did not find differences in dive frequency between incubation and late chick-rearing, even though several studies suggested an increase of parents foraging effort during chick-rearing (Shaffer et al 2003;Navarro et al 2007). Nevertheless, these studies considered chick-rearing as a single phase covering possible differences in birds' foraging activity over it.…”
Section: Effect Of Phase and Trip Type On Foraging Effortcontrasting
confidence: 79%
“…Later, parents reduced their mean trip length during chick-rearing phase. During this period, the energetic demands of the parents increase (Shaffer et al 2003;Navarro et al 2007), since they must feed both their chick and themselves. Our observations showed that Scopoli's shearwater foraging ecology changed also within the chickrearing period.…”
Section: Effect Of Phase and Trip Type On Foraging Effortmentioning
confidence: 99%
See 1 more Smart Citation
“…Foraging locations at sea, particularly distance to food, influence offspring feeding frequency (Pinaud et al 2005), reproductive success (Inchausti et al 2003), and adult energy balance (Shaffer et al 2003). How central-place foragers use the ocean affects not only their breeding parameters, but also their conservation, because of increasing conflicts between human activities and wildlife (Boersma 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For central-place foragers, distance to foraging areas is often related to trip duration and the frequency of offspring feeding (Shaffer et al 2003, Boersma et al 2007). Many seabirds and pinnipeds feed at particular oceanographic features (Hunt et al 1999, Boersma et al in press), and flying or swimming from breeding sites to the foraging areas make up a large percentage of the trip duration.…”
Section: Introductionmentioning
confidence: 99%